2022
DOI: 10.1075/ml.19002.gah
|View full text |Cite
|
Sign up to set email alerts
|

Spelling errors in English derivational suffixes reflect morphological boundary strength

Abstract: To what extent do speakers decompose morphologically complex words, such assegmentable, into their morphological constituents? In this article, we argue that spelling errors in English affixes reflect morphological boundary strength and degrees of segmentability. In support of this argument, we present a case study examining the spelling of the suffixes -able/-ible, -ence/-ance, and -mentin an online resource (Tweets), in forms such as <availible>, <invisable>, <eloquance>, and <bettermint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Moreover, the analyses revealed an effect of Bigram <d> support within the verb category: The more frequent a final bigram ending in <d> (e.g., <rd>) occurred in inflected verb forms compared to the verb-final bigram ending in <t> (e.g., <rt>) 27 (i.e., the higher the value of this ratio), the fewer errors were made on the partially homophonous past participles spelled with a <d> ending. This finding, i.e., an effect of Bigram <d> support, is consistent with the findings of Gahl & Plag (2019). In their study, they observed an effect of the variant bigram (i.e., the incorrectly spelled bigram) on the spelling of English derivational suffixes produced in tweets: The higher the probability of the variant bigram, the higher the probability that the spelling variant (i.e., a spelling error) occurred in the Twitter corpus (Gahl & Plag 2019: 20).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the analyses revealed an effect of Bigram <d> support within the verb category: The more frequent a final bigram ending in <d> (e.g., <rd>) occurred in inflected verb forms compared to the verb-final bigram ending in <t> (e.g., <rt>) 27 (i.e., the higher the value of this ratio), the fewer errors were made on the partially homophonous past participles spelled with a <d> ending. This finding, i.e., an effect of Bigram <d> support, is consistent with the findings of Gahl & Plag (2019). In their study, they observed an effect of the variant bigram (i.e., the incorrectly spelled bigram) on the spelling of English derivational suffixes produced in tweets: The higher the probability of the variant bigram, the higher the probability that the spelling variant (i.e., a spelling error) occurred in the Twitter corpus (Gahl & Plag 2019: 20).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, “receive” may be often misspelled as “recieve” because the bigram “ie” is more frequent in English than “ei,” and “tomorrow” misspelled as “tommorrow” because /m/ can be ambisyllabic (as in “summer”). The analogical force of language statistics may bias writers toward a spelling that is nonstandard (see Bar-On & Kuperman, 2019; Gahl & Plag, 2019, for relevant corpus analyses). Thus, longer processing times in words with greater spelling entropy may be caused by an underlying linguistic complexity, which leads to both an emergence of spelling errors and an increased cognitive effort of word recognition.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that these kinds of statistics is indeed available to readers (for studies of spelling errors see e.g., Bar-On & Kuperman, 2019;Gahl & Plag, 2019;Schmitz, Chamalaun, & Ernestus, 2018). Prior literature suggests that spelling errors can harm an individual's orthographic lexicon through passive exposure, even if the individual has a high spelling ability and does not independently produce such errors.…”
Section: Rationale and General Approachmentioning
confidence: 99%
“…Importantly, the occurrence of this error was much less likely if it would disrupt a morphological boundary. Gahl & Plag (2019) show that the strength of morphological boundaries affects misspellings of derivationally complex words in English. Drawing on Twitter data, they investigate cases in which the target suffix is replaced by a similarly-sounding suffix, e.g.…”
Section: State Of the Artmentioning
confidence: 91%